2020
DOI: 10.1021/acs.molpharmaceut.9b01179
|View full text |Cite
|
Sign up to set email alerts
|

Development of 18F-Fluoroglycosylated PSMA-Ligands with Improved Renal Clearance Behavior

Abstract: The prostate-specific membrane antigen (PSMA) is a type II transmembrane glycoprotein that is highly expressed in the malignant human prostate epithelium. Therefore, PSMA has emerged as a very attractive target for developing radiopharmaceuticals for the diagnosis, e.g., by positron emission tomography (PET) imaging, and radiotherapy of prostate cancer. The aim of this study was to develop 18

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Based on our previous experience in the development of 18 F-labeled glycoconjugates as PET imaging agents (27,28,32), the radiosynthesis of [ 18 F]FGlc-FAPI was started from precursor 1 (27) for 18 Fsubstitution, followed by 18 F-fluoroglycosylation of 11 (400 nmol) under optimized reaction conditions (Fig. 2).…”
Section: Chemistry and Radiochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous experience in the development of 18 F-labeled glycoconjugates as PET imaging agents (27,28,32), the radiosynthesis of [ 18 F]FGlc-FAPI was started from precursor 1 (27) for 18 Fsubstitution, followed by 18 F-fluoroglycosylation of 11 (400 nmol) under optimized reaction conditions (Fig. 2).…”
Section: Chemistry and Radiochemistrymentioning
confidence: 99%
“…We here report an alkyne-bearing version of FAPI-04 and its use as a precursor for the click chemistry-based synthesis of an 18 F-labeled FAP inhibitor. In previous studies, we demonstrated that the introduction of 18 F-labeled glycosyl moieties could positively influence the clearance behavior of a radiotracer (26)(27)(28), and the glycosylation of biomolecules has been frequently shown to improve the in vivo stability in blood and allows for the optimization of active drug delivery (29,30). Therefore, herein, we present the radiosynthesis and preclinical evaluation of an 18…”
Section: Introductionmentioning
confidence: 99%
“…The click chemistry strategy for 18 F-fluoroglcosylation using 2-deoxy-2 -[ 18 F]fluoroglucopyranosyl azide (2) or 6-deoxy-6-[ 18 F]fluoroglucopyranosyl azide (14) was applied to prostate-specific membrane antigen (PSMA) inhibitors of the glutamate-urealysine type to afforded 2-[ 18 F]FGlc-PSMA (21) and 6-[ 18 F]FGlc-PSMA (22) [44]. The 18 Ffluoroglycosylated PSMA inhibitors 21 and 22 were afforded in RAY of 19−22% and with molar activities of 71−136 GBq/µmol.…”
Section: -Deoxy-6-[ 18 F]fluoro-β-glycosyl Azides For Click Chemistry-based 18 F-fluoroglycosylationmentioning
confidence: 99%
“…with rapid clearance (0.9%ID/g at 120 min p.i.). Thus, the 6-fluoroglucosyl analog 22, with an adequate uptake in PSMA-positive tumors, a considerably low kidney uptake and fast clearance from the kidneys, it could be a promising radiotracer for translation into the clinic [44].…”
Section: -Deoxy-6-[ 18 F]fluoro-β-glycosyl Azides For Click Chemistry-based 18 F-fluoroglycosylationmentioning
confidence: 99%
“…with rapid clearance (0.9 %ID/g at 120 min p.i.). Thus, the 6-fluoroglucosyl analog 22, with adequate uptake in PSMA-positive tumors, its considerably low kidney uptake and fast clearance from kidneys, could be a promising radiotracer for translation into the clinic [45]. The 18 F-fluoroglycosylation via the clickable prosthetic group 14 was also applied to the first radiosynthesis of a neurotensin receptor 2 (NTS2)-subtype selective peptide ligand reported by Maschauer et al [46].…”
Section: -Deoxy-2-[ 18 F]fluoro-β-glucosyl Azide For Click Chemistry Based 18 F-fluoroglycosylationmentioning
confidence: 99%